Prognosis of Adolescent Migraine Headache - J Gordon Millichap (Pediatric Neurology Briefs)
The prevalence and evolution over 5 years of migraine without aura (MWOA) and migraineous disorder (MD) in 64 adolescent patients (34 girls and 30 boys, mean age 17.3 +/-1.1 years) were studied at the Institute of Neuropsychiatry, University of Palermo, Italy.